The Relationship between Career Advancement and Job Satisfaction among Teachers in Selected Public Secondary Schools in Igembe North, Kenya - Mwiti, Josphat; Moguche, Mr. Abel; Rintari, Dr. Nancy (Human Resource and Leadership Journal, 2021)
Purpose: Job satisfaction is viewed as a catalyst of improving performance and commitment in a workplace. The rationale of the study was to establish the relationship between career advancement and job satisfaction relating to secondary school teachers confined in Igembe North sub-county. The independent variable career advancement was used in coming up with the specific objective of the study as well as formulating hypothesis. The relationship of this predictor variable with the dependent variable job satisfaction among teachers was statistically established. The study would be useful to the following interested parties; TSC, BOM and heads of public secondary schools and to scholars. Methodology: The three theories which were relevant to the study were analysed to determine their relevance, strengths and weaknesses. They included equity, dual factor and hierarchy of needs theories of motivation. A descriptive survey design was applied as it was appropriate in obtaining quantitative data from the sampled respondents which was analysed quantitatively to describe the variables of the study. The study targeted 427 teachers who formed the total population of the study. Secondary schools were classified as boarding schools and day secondary schools in the sub-county through the application of a stratified technique of random sampling. A sample size equivalent to 129 teachers was selected representing thirty per cent of the target population. A five Likert scale closed-ended questionnaire was utilised to gather quantitative data from the selected teachers. To assess how the questionnaire was reliable and valid in accomplishing its intended task, seven teachers from Igembe South sub-county were selected for piloting purposes. This was achieved by applying a test and re-test technique. Cronbach's alpha coefficient of 0.794 was obtained which was above the recommended value of atleast 0.7. Descriptive and inferential statistical tools were applied in analysing the data. Regression analysis was utilised to establish the extent to which the predictor variable influenced the response variable. For easier interpretation of the data, pie charts and tables of distributions were deemed appropriate. Results: The study findings revealed that career advancement had a mean of 3.52 which moderately showed that the respondents agreed that it impacted positively on job satisfaction. Further, career advancement had r = 0.8902 indicating a strong positive correlation with job satisfaction. It had a beta coefficient of 0.4082 and a p-value of 0.0017. These statistical results of the findings manifested clearly that the relationship between career advancement and job satisfaction was positive and significant. Unique contribution to theory, policy and practice: Therefore, the study recommends that schools Board of Management and principals should continue organising and facilitating workshops and seminars in their schools to equip teachers with relevant skills in the areas of ICT integration, communication and management among others. The secondary school principals should increase monitoring their teachers' training gaps to expand their skill set. The Teachers' Service Commission (TSC) should liaise with the Ministry of Education on the way forward to offering free or subsidised training to teachers to widen their career paths. The study also recommends that non-monetary rewards such as workshops and seminars should be considered and incorporated in the rewarding systems adopted by public secondary schools.